1991
DOI: 10.1007/bf02190701
|View full text |Cite
|
Sign up to set email alerts
|

Effects of in vivo manganese administration on calcium exchange and contractile force of rat ventricular myocardium

Abstract: The purpose of this study was to investigate the effect of prolonged (14 days) intragastric administration of Mn2+ (0.25 mmol/kg daily) on Ca2+ exchange and contractility of rat ventricular myocardium. Left-ventricular pressure and its first derivative (dP/dt) were recorded by means of a balloon catheter inserted via the left atrium into the left ventricle of the rat heart perfused by Langendorff method. Ca2+ exchange in the stimulated and rested ventricular myocardium was investigated with the aid of 45Ca und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 28 publications
0
11
1
Order By: Relevance
“…Fourteen days following Mn exposure, the exchangeable Ca in the Mntreated group was increased by 52% as compared with controls. By recording the leftventricular pressure (dP/dt) via a balloon catheter inserted into the left ventricle, the authors also observed that the maximal ventricular developed pressure (P max ) and the maximal leftventricular pressure (dP/dt max ) were increased by 35% and 228%, respectively, in comparison with control rats, following 14 d of Mn administration (27).…”
Section: Mn Exposure and Cardiac Ca Statusmentioning
confidence: 94%
“…Fourteen days following Mn exposure, the exchangeable Ca in the Mntreated group was increased by 52% as compared with controls. By recording the leftventricular pressure (dP/dt) via a balloon catheter inserted into the left ventricle, the authors also observed that the maximal ventricular developed pressure (P max ) and the maximal leftventricular pressure (dP/dt max ) were increased by 35% and 228%, respectively, in comparison with control rats, following 14 d of Mn administration (27).…”
Section: Mn Exposure and Cardiac Ca Statusmentioning
confidence: 94%
“…The effects of long-lasting exposures are however less clear. A Mn++, intragastric ratfeeding study over 14 days (0.25 mmollkg daily) resulted in increased myocardial contractility (4). Work exposure to manganese was estimated from 339 personal samples of total dust and total manganese during 1979-1991 in the largest of the FeMnISiMn plants; the results showed decreasing values during this period ( figure I).…”
Section: Discussionmentioning
confidence: 99%
“…possible with exposure to manganese alloys, as animal studies have shown that the divalent manganese ion (Mn++) may influence cardiac function (3,4).…”
mentioning
confidence: 99%
“…41,47 It is known as an intracellular agent, rapidly up-taken (within minutes 8,29,54 ) by L-type Ca 2+ channels, 26 and released extremely slowly [within time intervals ‡5-10 min] (with reported excretion half-times of a fast and a slow component of 4 and 39 days, respectively 29 ) from the intracellular space via the Na + -Ca 2+ exchanger. 14,28,34 In fact, Mn 2+ accumulation in rat myocardium has been associated with the Na + -Ca 2+ exchanger, based on its MRI T 2 * effects under experimentally induced hyperkalemic hypoxia conditions. 35 In support of such action by the exchanger for Mn 2+ transport kinetics, were also sodium-potassium ATPase blockade studies in bullfrog ventricles by Brommundt et al, 5 as well as evidence for bidirectional activity of the Na + -Ca 2+ exchanger, mediating cellular Mn 2+ influx, and efflux.…”
Section: Abbreviationsmentioning
confidence: 99%
“…To date its exact mechanism of action is still not completely comprehended, but it is suggested to act as a Ca 2+ analogue. 14,26,56 Its effects on mouse cardiac function have not been addressed extensively, with its molecular mechanisms on intracellular targets being largely unknown and unproved. Based on experimental results from a series of invasive catheterizations, this study examines the temporal stability of hemodynamic indices of systolic and diastolic function in C57BL/6 mice under isoflurane (ISO) anesthesia conditions (employing the same protocol widely used in MRI/microCT studies), and the effects of Mn 2+ on the mouse hemodynamic response as a potential modulator of myocardial force generation.…”
Section: Abbreviationsmentioning
confidence: 99%